2012
DOI: 10.1088/0004-637x/752/2/78
|View full text |Cite
|
Sign up to set email alerts
|

PANCHROMATIC OBSERVATIONS OF SN 2011dh POINT TO A COMPACT PROGENITOR STAR

Abstract: We report the discovery and detailed monitoring of X-ray emission associated with the Type IIb SN 2011dh using data from the Swift and Chandra satellites,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
142
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(159 citation statements)
references
References 53 publications
15
142
2
Order By: Relevance
“…Optical and NIR photometry and spectroscopy, mainly from the first 50 days, have been published by A11, M11, Tsvetkov et al (2012, hereafter T12), Vinkó et al (2012, hereafter V12), Marion et al (2013, hereafter M13), Van Dyk et al (2013, hereafter D13) and Sahu et al (2013, hereafter S13). Radio and millimeter observations have been published by Martí-Vidal et al (2011), Krauss et al (2012), Bietenholz et al (2012), Soderberg et al (2012) and Horesh et al (2013) and X-ray observations by Soderberg et al (2012), Sasaki & Ducci (2012) and Campana & Immler (2012). The SN has been monitored in the ultraviolet (UV) using Swift, in the mid-infrared (MIR) using Spitzer and at sub-millimeter wavelengths using Herschel.…”
Section: Supernova 2011dhmentioning
confidence: 99%
See 2 more Smart Citations
“…Optical and NIR photometry and spectroscopy, mainly from the first 50 days, have been published by A11, M11, Tsvetkov et al (2012, hereafter T12), Vinkó et al (2012, hereafter V12), Marion et al (2013, hereafter M13), Van Dyk et al (2013, hereafter D13) and Sahu et al (2013, hereafter S13). Radio and millimeter observations have been published by Martí-Vidal et al (2011), Krauss et al (2012), Bietenholz et al (2012), Soderberg et al (2012) and Horesh et al (2013) and X-ray observations by Soderberg et al (2012), Sasaki & Ducci (2012) and Campana & Immler (2012). The SN has been monitored in the ultraviolet (UV) using Swift, in the mid-infrared (MIR) using Spitzer and at sub-millimeter wavelengths using Herschel.…”
Section: Supernova 2011dhmentioning
confidence: 99%
“…Using approximate models A11 argued that the SN cooled too fast and Soderberg et al (2012) that the speed of the shock was too high to be consistent with an extended progenitor. However, in B12 we have used detailed hydrodynamical modelling to show that a 3.3-4 M helium core with an attached thin and extended hydrogen envelope well reproduces the early photometric evolution and is also consistent with the temperature inferred from early spectra.…”
Section: Supernova 2011dhmentioning
confidence: 99%
See 1 more Smart Citation
“…Collisions of matter outside the star might also occur and significantly influence the observational features of the resulting transient. Matzner et al (2013) discussed SN 2011dh in the context of oblique shock breakout, and suggested that the resulting asphericity of the highest-velocity ejecta might explain why the early-time luminosity and radio emission indicated a compact progenitor (Arcavi et al 2011;Soderberg et al 2012), even though post-explosion images clearly showed that the SN stemmed from an extended YSG (Van Dyk et al 2013); the reason for the discrepancy lies in the unrealistic assumption of spherical symmetry. Interestingly, oblique shock breakout in SN 2011dh might also explain why the SN exhibited the strongest continuum polarization during the earliest stages, since the photosphere was in the outer envelope of the quasihomologous flow where velocities are highest.…”
Section: Oblique Shock Breakoutmentioning
confidence: 99%
“…Remarkably, a yellow supergiant (YSG) star was found to be spatially coincident with the SN in HST archival images of the galaxy Maund et al 2011;Van Dyk et al 2011). It was unclear whether this star was the actual progenitor of the explosion, a neighbor, or even a surviving companion star to a more compact progenitor as initially hypothesized on the basis of its early-time luminosity (Arcavi et al 2011) and radio emission (Soderberg et al 2012). Eventually, the identification of the YSG as the true progenitor was solidified after the SN had faded, revealing that the YSG star had disappeared (Van Dyk et al 2013).…”
Section: Introductionmentioning
confidence: 98%